Exercise-Induced Lactate Release Mediates Mitochondrial Biogenesis in the Hippocampus of Mice via Monocarboxylate Transporters - Park, Jonghyuk; Kim, Jimmy; Mikami, Toshio (Frontiers in Physiology, 2021)
Regular exercise training induces mitochondrial biogenesis in the brain via activation of peroxisome proliferator-activated receptor gamma-coactivator 1α (PGC-1α). However, it remains unclear whether a single bout of exercise would increase mitochondrial biogenesis in the brain. Therefore, we first investigated whether mitochondrial biogenesis in the hippocampus is affected by a single bout of exercise in mice. A single bout of high-intensity exercise, but not low- or moderate-intensity, increased hippocampal PGC-1α mRNA and mitochondrial DNA (mtDNA) copy number at 12 and 48 h. These results depended on exercise intensity and blood lactate levels observed immediately after exercise. As lactate induces mitochondrial biogenesis in the brain, we examined the effects of acute lactate administration on blood and hippocampal extracellular lactate concentration by in vivo microdialysis. Intraperitoneal (I.P.) lactate injection increased hippocampal extracellular lactate concentration to the same as blood lactate level, promoting PGC-1α mRNA expression in the hippocampus. However, this was suppressed by administering UK5099, a lactate transporter inhibitor, before lactate injection. I.P. UK5099 administration did not affect running performance and blood lactate concentration immediately after exercise but attenuated exercise-induced hippocampal PGC-1α mRNA and mtDNA copy number. In addition, hippocampal monocarboxylate transporters (MCT)1, MCT2, and brain-derived neurotrophic factor (BDNF) mRNA expression, except MCT4, also increased after high-intensity exercise, which was abolished by UK5099 administration. Further, injection of 1, 4-dideoxy-1,4-imino-D-arabinitol (DAB; glycogen phosphorylase inhibitor) into the hippocampus before high-intensity exercise suppressed glycogen consumption during exercise, but hippocampal lactate, PGC-1α, MCT1, and MCT2 mRNA concentrations were not altered after exercise. These results indicate that the increased blood lactate released from skeletal muscle may induce hippocampal mitochondrial biogenesis and BDNF expression by inducing MCT expression in mice, especially during short-term high-intensity exercise. Thus, a single bout of exercise above the lactate threshold could provide an effective strategy for increasing mitochondrial biogenesis in the hippocampus.